Indefinite Integration of ex

Indefinite Integration of e^x

How to solve the indefinite integration of ex problems: formula, example, and its solution.

Formula

(integral of e^x dx) = e^x + C

ex dx = ex + C

This is true because
[ex + C]' = ex.

Derivative of ex

Example

Find the given indefinite integral. The integral of [(e^2x - 1) / (e^x - 1)] dx

(ex)2 - 12 = (ex + 1)(ex - 1)

Factoring the difference of squares

Cancel (ex - 1)
on both of the numerator and the denominator.

ex dx = ex

So (given) = ex + x + C.